Liquids on-chip: direct storage and release employing micro-perforated vapor barrier films. Issue 13 (7th July 2015) - Czurratis, Daniel; Beyl, Yvonne; Grimm, Alexander; Brettschneider, Thomas; Zinober, Sven; Lärmer, Franz; Zengerle, Roland
<x xml:space="preserve">Abstract</x> Liquids on-chip describes a reagent storage concept for pressure driven Lab-on-Chip (LoC) devices, which enables liquid storage in reservoirs without additional packaging. In addition to PC/TPU, we suggest a novel polymer composite based on COP and TPS suitable for laser welding.